Pengaruh Kepercayaan, Pemasaran Online, Citra Merek dan Keputusan Pembelian terhadap Loyalitas Pelanggan - Khotimah, Khusnul; Pawirosumarto, Suharno; Lusiana, Lusiana; Sari, Silvia; Fitria, Lailani; Yani, Ahmad; Rafky, Rafnelly; Oktarina, Yolanda; Nofriadi, Nofriadi (Dinasti Review, 2023)
The Influence of Trust, Online Marketing, Brand Image, and Purchasing Decisions on Customer Loyalty is a scientific literature study article within the scope of Marketing Management Science. The aim of this article is to build a hypothesis of influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method uses the research library sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Trust influences customer loyalty; 2) Online marketing influences customer loyalty; 3) Brand image influences customer loyalty; and 4) Purchasing decisions influence customer loyalty.